ANALYSIS OF AMERICA, CHINA, AND INDONESIAN CONFLICT STYLES IN THE SOUTH CHINA SEA 2018-2023 - Hanif Zaki, Amril AHZ (UI Scholars Hub, 2024)
This research aims to analyse the factors contributing to the ongoing conflict in the South China Sea between China, Indonesia, and the United States. China's aspiration to control the Natuna Islands has been evident since the 1990s, with a marked escalation since 2009. The authors used a mixed methods approach, including a literature review and bibliometric analysis, to analyse 49 documents from the Scopus database. Data were analysed using the 50 Conflict Resolution Activities framework by Jonamay Lambert and Selma Meyers. The study reveals that China exhibits a “Pit Bull” conflict style in 2019 documents, while the United States and Indonesia demonstrate a “Worker Bees” conflict style in 2019, 2020, and 2023 documents. Indonesia is expected to be diligent in 2021, 2022, and 2023 documents. Conflict escalation in the South China Sea involving China, Indonesia, and the United States experienced a spike in 2019-2020 documents, resembling the behaviour of a